Patients co-infected with hepatitis C virus (HCV) and human immunodeficiency virus recover genotype cross-reactive neutralising antibodies to HCV during antiretroviral therapy - Lee, S.; Saraswati, H.; Yunihastuti, E.; Gani, R.; Price, Patricia (Academic Press, 2014)
When severely immunodeficient HIV/HCV co-infected patients are treated with antiretroviral therapy, it is important to know whether HCV-specific antibody responses recover and whether antibody profiles predict the occurrence of HCV-associated immune restoration disease (IRD). In 50 HIV/HCV co-infected patients, we found that antibody reactivity and titres of neutralising antibodies (nAb) to JFH-1 (HCV genotype 2a virus) increased over 48 weeks of therapy. Development of HCV IRD was associated with elevated reactivity to JFH-1 before and during the first 12 weeks of therapy. Individual analyses of HCV IRD and non-HCV IRD patients revealed a lack of an association between nAb responses and HCV viral loads. These results showed that increased HCV-specific antibody levels during therapy were associated with CD4+ T-cell recovery. Whilst genotype cross-reactive antibody responses may identify co-infected patients at risk of developing HCV IRD, neutralising antibodies to JFH-1 were not involved in suppression of HCV replication during therapy.